Visualizing Archaeologies: A Manifesto - RUSSELL, IAN (My University, 2007)
Is archaeology a science? Is archaeology a humanity? What are the politics of spectatorship and archaeological representation? These initial thoughts form the basis for our archaeological explorations. Within current archaeological discourse, there are a growing number of requests for expressions, which illuminate and expose the interpretive and artistic qualities of presentation and narration. Yet few scholars actively utilize expressive practice to explore these philosophical issues. As such, we feel that it is an opportune time to intervene in visual and textual discourse by issuing a manifesto for our project. We call for a development of a critically reflexive practice of visual archaeological expressionism, which seeks to contest traditional modes of thought and action.
PUBLISHED
Keywords: archaeology; art; archaeological theory; visual cultural theory